2020
DOI: 10.1101/2020.07.15.204560
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Interleukin-10 suppression enhances T-cell antitumor immunity and responses to checkpoint blockade in chronic lymphocytic leukemia

Abstract: T-cell dysfunction is a hallmark of B-cell Chronic Lymphocytic Leukemia (CLL). CLL cells downregulate T-cell responses by expressing regulatory molecules including programmed death ligand-1 (PD-L1) and Interleukin-10 (IL-10). Immune checkpoint blockade (ICB) aims to restore T-cell function by preventing the ligation of inhibitory receptors like PD-1, however most CLL patients do not respond well to this therapy. Thus, we investigated whether IL-10 suppression could enhance antitumor T-cell activity and improve… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Further, as previously reported, BTLA blockade decreased the production of the immunosuppressive and tumor-promoting cytokine IL-10 by B cells, suggesting that targeting BTLA signaling may restore, at least in part, NK cell immune competence [ 48 , 68 , 69 , 70 ]. Importantly, a recent work has showed that inhibition of IL-10 boosts ICB-related anti-tumor responses in CLL [ 71 ]. In line with this, BTLA blockade promoted NK cell-mediated cytotoxicity and rituximab-induced ADCC in CLL.…”
Section: Discussionmentioning
confidence: 99%
“…Further, as previously reported, BTLA blockade decreased the production of the immunosuppressive and tumor-promoting cytokine IL-10 by B cells, suggesting that targeting BTLA signaling may restore, at least in part, NK cell immune competence [ 48 , 68 , 69 , 70 ]. Importantly, a recent work has showed that inhibition of IL-10 boosts ICB-related anti-tumor responses in CLL [ 71 ]. In line with this, BTLA blockade promoted NK cell-mediated cytotoxicity and rituximab-induced ADCC in CLL.…”
Section: Discussionmentioning
confidence: 99%
“…This notion is supported by recent work showing that targeted delivery of miR-29b to CLL cells leads to enhanced cellular reprogramming and decreased viability due to its effect of decreasing SP1 expression [31]. Furthermore, mtm analogs have been shown to be effective against CLL cells, with EC-7072 inducing CLL cell death through targeting of BCR signaling [32], and administration of MTM OX 32E to the Eμ-Tcl1 mouse model reduces the malignant cell burden [33].…”
Section: Discussionmentioning
confidence: 83%
“…As a tumor progresses, high levels of IL-10 exhibit powerful immunosuppressive effects through inhibiting the proliferation of T cells and the production of cytokines such as IFN-γ and IL-2 ( 159 ). IL-10 suppression was found to enhance the antitumor activity against CLL ( 161 ). In addition, combining T-cell therapy with treatments targeting immune cell PD-1 showed high efficacy against leukemia via the production of more IFN-γ, the increasing of cytolytic functions, and the increasing of memory CD8 + T cells ( 161 ).…”
Section: The Challenges Of Adoptive Tcr-t Cell Immunotherapy For Amlmentioning
confidence: 99%
“…IL-10 suppression was found to enhance the antitumor activity against CLL ( 161 ). In addition, combining T-cell therapy with treatments targeting immune cell PD-1 showed high efficacy against leukemia via the production of more IFN-γ, the increasing of cytolytic functions, and the increasing of memory CD8 + T cells ( 161 ).…”
Section: The Challenges Of Adoptive Tcr-t Cell Immunotherapy For Amlmentioning
confidence: 99%